Effects of microcystin-LR in isolated perfused rat kidney - Nobre,A.C.L. (1999)
Microcystin is a hepatotoxic peptide which inhibits protein phosphatase types 1 and 2A. The objective of the present study was to evaluate the physiopathologic effects of microcystin-LR in isolated perfused rat kidney. Adult Wistar rats (N = 5) of both sexes (240-280 g) were utilized. Microcystin-LR (1 µg/ml) was perfused over a period of 120 min, during which samples of urine and perfusate were collected at 10-min intervals to determine the levels of inulin, sodium, potassium and osmolality. We observed a significant increase in urinary flow with a peak effect at 90 min (control (C) = 0.20 ± 0.01 and treated (T) = 0.32 ± 0.01 ml g-1 min-1, P<0.05). At 90 min there was a significant increase in perfusate pressure (C = 129.7 ± 4.81 and T = 175.0 ± 1.15 mmHg) and glomerular filtration rate (C = 0.66 ± 0.07 and T = 1.10 ± 0.04 ml g-1 min-1) and there was a significant reduction in fractional sodium tubular transport at 120 min (C = 78.6 ± 0.98 and T = 73.9 ± 0.95%). Histopathologic analysis of the perfused kidneys showed protein material in the urinary space, suggestive of renal toxicity. These data demonstrate renal vascular, glomerular and urinary effects of microcystin-LR, indicating that microcystin acts directly on the kidney by probable inhibition of protein phosphatases.